The effectiveness of using electronic educational platforms in achieving learning outcomes in light of the Corona pandemic, "The Saudi Experience" - Al-Baqmi, Muhammad Mutheeb Suqan; Salem, Osama Mohamed Ahmed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the effectiveness of using electronic educational platforms in achieving learning outcomes in light of the Corona pandemic, the “Saudi experience.” The researcher used the descriptive approach. The questionnaire as a tool for collecting data and information related to the research, and it consisted in its final form of (50) paragraphs, distributed over four axes. My calculation (4.02 out of 5) for teachers, and (3.69) for students, and that the level of obstacles to the use of electronic learning platforms in achieving learning outcomes in light of the Corona pandemic from the teachers' point of view was at a high degree, and with an arithmetic average (4.01), and that the level of mechanisms for activating the use of educational platforms E-learning in achieving learning outcomes in light of the Corona pandemic from the teachers’ point of view was at a high degree and with an arithmetic mean (3.92), and that there are statistically significant differences between the average responses of the study sample about There are mechanisms for activating the use of e-learning platforms in achieving learning outcomes due to the variable of sex, in favor of teachers and the variable of specialization, in favor of scientific specializations, and in terms of years of experience, in favor of those with experience (10) years or more versus other categories of experience, and in favor of those with experience (5 to less than 10) years versus less than (5) years. The study recommended the need to provide a guide for the uses of electronic educational platforms in the education resource rooms in schools supervised by the Ministry of Education, and to hold continuous meetings with those in charge of distance teaching to identify the mechanisms for overcoming the obstacles to using electronic educational platforms and educating them about how to overcome them.
Keywords: e-learning; educational platforms; learning outcomes; Corona pandemic